MECOM gene overexpression in pediatric patients with acute myeloid leukemia. (3rd April 2022) - Elsherif, Mariam; Hammad, Mahmoud; Hafez, Hanafy; Yassin, Dina; Ashraf, Mohamed; Yasser, Nouran; Lehmann, Leslie; Elhaddad, Alaa
Abstract: Background: Acute myeloid leukemia (AML) is characterized by blocked or aberrant differentiation of hematopoietic stem cells. The MECOM gene overexpression in hematopoietic progenitors induces myeloid differentiation block, resulting in increased self-renewal and survival of these transformed progenitors. However, its exact role in AML remains unclear. We aimed to estimate the prevalence of MECOM overexpression among pediatric AML patients, and assess its impact on clinical outcome. Patients and Methods: Real-time quantitative polymerase chain reaction and Livak method (2 ΔΔCt ) were used to determine relative MECOM expression level among 243 pediatric patients with AML. MECOM overexpression was considered if the cumulative relative expression was above 1 (2 -ΔΔCt ) and was designated as MECOM pos . Results: Of 243 AML patients tested 57(23.5%) demonstrated MECOM pos . Patients with MECOM pos had significantly lower median age. The frequency of MECOM pos was significantly higher among AML patients with 11q23 abnormalities, complex karyotypes and among high- and intermediate-risk groups compared to low-risk group ( p = .014). MECOM pos patients had significantly lower overall survival (OS) (38.7 vs. 78.9%, p < .001), event-free survival (EFS) (37.3% vs. 68.4%, p < .001), and had higher cumulative incidence of relapse (49.5% vs. 23.5%, p = .002) at 36 months compared to MECOM neg patients. Multivariate analysis revealed that MECOM pos was an adverse prognostic factor for OS (hazards ratio (HR) = 2.11, 95% confidence interval (CI) 1.24–3.60, p = .006) and EFS (HR= 1.71, 95% CI 1.07–2.75, p = .025). The logistic regression model showed that MECOM pos was an independent prognostic factor regardless of minimal residual disease status post first induction therapy in the intermediate-risk group (odds ratio 2.89; 95% CI 1.19–6.57, p = .018). Conclusion: The aberrant MECOM gene expression is an adverse prognostic factor, especially in patients without previously known cytogenetic risk factors. Our results suggest the potential benefit from pretreatment screening for MECOM gene overexpression in newly diagnosed AML patients for better risk stratification and treatment adjustment.